STUDI KEBERSIHAN PASAR INPRES BALAI SELASA DI NAGARI KOTO NAN IV KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - jufri mansyah, Medis; Drs. Edi Suarto, M.Pd, Slamet; Yuherman, SP., M.Pd, Yuherman, SP., M.Pd (Pendidikan Geografi, 2014)
ABSTRACK             In the market is fery neede hygiene cooperation between market services and merchants as well as a high concern in maintaining the cleanliness of the market in order to create a healthy market, clean, comfortable and a better maket for the foreseable future. This reasech aims to describe the market cleanliness in balai selasa at Nagari Koto Nan IV Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan.                This reseach is qualitative reseach with reseaach sites in the market hall inpres balai selasa in Nagari Koto Nan IV Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan. The informant in this reseach are: office market, janitor, existing traaders in that market. This reseach used techniques of documentation, observation, and interviews. The accuracy of the data was tested by using triangulation of data, from the data that have been collected, the reseacher analized the data by using purposive sampling model that consists of data collection, data reduction, data display and conglicion. The results showed that: the cleanliness of the thaditional market in inpres balai selasa in Nagari Koto Nan IV Kecamatan Ranah Pesisir Kabupaten Pesisir Selatan are(1) awareness of traders in the market hygiene remains low, because many traders are not collecting their garbage, (2) knowledge of the merchant in maintaining poor hygiene market, because there is no trashservice provided by the market, (3) maintaining the cleanliness habits of traders in the market shows that the number of traders who do not dispose waste in the nigh place.